Establishing Reliability and Validity for a Professional Development Tool for Graduate Health Care Programs. - Handler, Lisa; Waldman-Levi, Amiya (Open Journal of Occupational Therapy (OJOT))
Professional development ensures practitioners develop the necessary skills to succeed in multifaceted clinical roles. To provide evidence-based best practices, health practitioners need to possess critical thinking, executive functioning, and emotional intelligence skills. Study aimed to establish psychometric properties to the Inventory of Professional and Academic Reasoning (IPAR). Two cross-sectional studies of reliability and validity were used. The participants included 139 health profession students, of which 93 students participated in the first study and 46 occupational therapy students participated in the second study. Data were collected online and at fieldwork sites using a background questionnaire, IPAR, Executive Function Index, and the Student Evaluation of Level I Fieldwork. IPAR reliability was found satisfactory. No significant differences were found between students' IPAR ratings across health professions programs. A discrepancy between students' self-rating of professional skills and the supervisor's evaluation of clinical competencies was found. The consistent pattern of overestimation of IPAR competencies suggests a gap in student self-awareness with actual practice skills. The IPAR can enhance the advisement process to support students' professional development. It will enable students to gain insight into their strengths and weaknesses as they enter their respective fields.